Pengembangan Rencana Induk Sistem Pemerintahan Berbasis Elektronik Provinsi Bali - Muka, I Wayan; Widyatmika, Made Adi; Putra, I Ketut Gde Darma (Badan Riset dan Inovasi Daerah Provinsi Bali, 2020)
Purpose: The purpose of this study is to obtain data from each OPD of the Province of Bali related to the implementation of E-Government (SPBE), determine the conditions of implementing E-Government (SPBE) in the Province of Bali and determine strategic steps to increase the level of maturity index of the SPBE of the Province of Bali. Research methods: The evaluation evaluation method is done through measuring the level of maturity based on the e-Government Maturity Model (eMM). Findings: This study revealed that the main weaknesses in the implementation of SPBE in Bali Province, especially in some OPDs that provide public services, were the lack of integration of applications or systems and the still weak human resources and IT infrastructure in each OPD. Implications: The steps that need to be taken are to formulate the SPBE Development Master Plan which has completeness on the side of the SPBE vision and mission load, SPBE architecture, SPBE road map as well as the integration of application systems and the use of general applications as a whole.